Mining, risk and climate resilience in the 'other' Pacific: Latin American lessons for the South Pacific1. (August 2015) - Bebbington, Anthony J.; Bury, Jeffrey; Cuba, Nicholas; Rogan, John
Abstract We suggest the value of considering Pacific Latin America and the South Pacific in relationship to each other in contexts of climate change and investment in extractive industry. The paper explores the interactions between extractive industry, climate change and environmental governance through the lenses of double exposure, double movements, resilience and risk. The first part of the paper addresses the nature and scope of investments in extractive industries in this 'other Pacific'. The geography of these investments is changing the actual and perceived distribution of exposure and risk in the region. The nature of this risk is also being affected by climate change and its implications for the geographies of water and land‐use. Much of the contention surrounding extractive industries can be understood as conflicts over the unequal distribution of this risk, how to interpret its significance and the ways in which resilience might be enhanced to respond to it. The final section of the paper discusses the ways in which mining governance and governance for resilience converge and, on the basis of recent experiences in El Salvador, analyses the difficulties in governing extractive industry in a way that manages risk and builds resilience.